Točnost metakognitivnih ocen v različnih razvojnih obdobjih - Bakračevič Vukman, Karin (Anthropos (Ljubljana), 2004)
Metacognition belongs to higher-order mental processes and enables us to control and plan our own mental activities. It has important effect on cognitive performance in children and adults. Metacognition leads us in selection and evaluation of cognitive taskas, in detection of mistakes in the solving process, in choosing goals and solving strategies. It was our aim in this research to investigate developmental differences in some metacognitive variables in problem-solving: metacognitive experiences and metacognitive knowlwdge. In the research participated 80 subjects of two different age groups: 40 nine to ten years old and 40 thirteen to fourteen years old subjects. They solved two well-defined and two ill-defined problems. After every problem they had to solve a metacognitive statements questionnaire. results showed us that the main difference between the groups occured in the field of metacognitive knowledge about problems, while metacognitive experiences seem to function quite accurate already in earlier years.
Keywords: developmental psychology; razvojna psihologija; metacognition; metakognicija; problem solving; reševanje problemov; cognitive development; kognitivni razvoj